The role of literary-artistic texts in the development of value criteria of younger primary school students - Čutović Mirjana M.; Semiz Marina Ž (University of Kragujevac - Faculty of Pedagogy, Užice, 2022)
Fundamental human values such as tolerance, respect for diversity, mutual help, generosity, honesty, kindness, trust, and fairness are highly moral values that can be encouraged among younger primary school students through the implementation of literary and artistic content in literature classes. Introducing students to the value categories and their acceptance can greatly contribute to preventing potential problems and inadequate behavior of children in communication with their peers and parents. Using a method of content analysis, the present paper considers some ways of encouraging the development of value criteria through the use of both curricular and extracurricular literary texts in Serbian language and literature classes in younger primary schools. The sample comprised 25 literary texts, 8 of which are taken from the Serbian Reader for the 3 rd grade and 17 texts are taken from the Serbian Reader for the 4th grade. The results indicate that the analyzed texts encourage the development of various value criteria among younger primary school children, the most frequently represented being honesty, tolerance, and respect for diversity. In addition, the paper represents a small contribution to the promotion of value criteria in the curricula and study programs, with the aim of more effectively eliminating negative forms of behavior and encouraging positive behavior among children.